Diffusing human trafficking policy in Eurasia - Dean, Laura A. (Policy Press, 2020)
Offering a perceptive study of the urgent human rights issue of trafficking in persons, this important book analyses the development and effectiveness of public policies across Eurasia. Drawing on multi-method research in the region, Laura A. Dean explores the factors behind anti-trafficking strategies and the role of governments and activists in combating labour and sexual exploitation. She examines the intersection of global strategies and state-by-state approaches, and uses the diffusion of innovation framework to cast new light on the impetus and implementation of different policy typologies. Identifying the strengths, weaknesses, and best practices in human trafficking policies around Eurasia, Dean's book will appeal to a wide range of students, scholars, practitioners, and policy makers